2011
DOI: 10.1007/s10886-011-9920-9
|View full text |Cite
|
Sign up to set email alerts
|

Release of Hydrogen Cyanide via a Post-secretion Schotten-Baumann Reaction in Defensive Fluids of Polydesmoid Millipedes

Abstract: Mandelonitrile benzoate, a minor defense component produced by polydesmoid millipedes, is produced in large amounts together with hydrogen cyanide following shake-disturbances administered to individuals of Nedyopus tambanus tambanus, Parafontaria tonominea, Epanerchodus sp., and Epanerchodus fulvus. These species commonly produce mandelonitrile and benzoyl cyanide (the oxidized product after discharge). The newly generated mandelonitrile benzoate was identified as a product of post secretion Schotten-Baumann … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…However, in B. troglobius (as in other analyzed species belonging to the genus Brachydesmus; Makarov et al, 2010) we could not found mandelonitrile, and it is difficult to include the analyzed species in either of the two groups of cyanogenic millipedes, as suggested by Kuwahara et al (2011). On the other hand, the presence of mandelonitrile benzoate in defensive fluids may be the mechanism that stabilizes mandelonitrile if the specimen is consumed by a predator; in such cases this compound will be degraded during passage through the digestive tract, as proposed for some cyanogenic glucosides in Zygaena larva by Zagrobelny and Møller (2011).…”
Section: Chemical Defense In the Brachydesmus Troglobiusmentioning
confidence: 63%
See 1 more Smart Citation
“…However, in B. troglobius (as in other analyzed species belonging to the genus Brachydesmus; Makarov et al, 2010) we could not found mandelonitrile, and it is difficult to include the analyzed species in either of the two groups of cyanogenic millipedes, as suggested by Kuwahara et al (2011). On the other hand, the presence of mandelonitrile benzoate in defensive fluids may be the mechanism that stabilizes mandelonitrile if the specimen is consumed by a predator; in such cases this compound will be degraded during passage through the digestive tract, as proposed for some cyanogenic glucosides in Zygaena larva by Zagrobelny and Møller (2011).…”
Section: Chemical Defense In the Brachydesmus Troglobiusmentioning
confidence: 63%
“…Finding of the mandelonitrile benzoate is interesting in the light of recent papers of Kuwahara et al (2011). These authors found that mandelonitrile benzoate is produced in large amounts together with hydrogen cyanide following shake-disturbances administered to several polydesmoid species.…”
Section: Resultsmentioning
confidence: 99%
“…This group, known as cyanogenic (sensu Eisner et al 1978) millipedes, is the largest and is composed of seven families that emit hydrogen cyanide derived from mandelonitrile (D). Kuwahara et al (2011) reported that 11 out of 14 Japanese polydesmid species they studied (with the exception of three non-cyanogenic species discussed later) could be separated into two groups based on defense chemistry: type-A [five species that use a mixture of mandelonitrile (D) and its degradation products, benzaldehyde (A) and hydrogen cyanide], and type-B [six species that use a mixture of mandelonitrile (D), benzaldehyde (A), hydrogen cyanide, benzoyl cyanide (B), mandelonitrile benzoate (E), and benzoic acid (C)] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although no taxonomic evidence currently is available for support, type-B millipedes have been proposed as the more advanced species, releasing hydrogen cyanide and mandelonitrile benzoate (E), generated through the SchottenBaumann reaction between mandelonitrile (D) and its oxidization product benzoyl cyanide (B), when attacked and/ or wounded (Kuwahara et al 2011). The involvement of the enzyme(s) responsible for that reaction also has been proposed for the oxidation of D to B (Kuwahara et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In case of threat or attack, the cyanogenic compounds are discharged and must be quickly degradable to release HCN. Known HCN storage compounds of mandibulate arthropods include aromatic or aliphatic glycosides, lipids, and cyanohydrins (e.g., mandelonitrile) (2,12,15).…”
mentioning
confidence: 99%